UPAYA PENINGKATAN KETERAMPILAN MENULIS CERPEN SISWA KELAS XI MIPA 4 MAN 2 BREBES DENGAN STRATEGI PEMBELAJARAN BERBASIS MASALAH - ETI SOPHIA WIJAYANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to describe the improvement of short story writing skills of Class XI MIPA 4 students of MAN 2 Brebes in learning to write short stories through the use of problem-based learning strategies. The results of this study indicate that the average score for writing pre-action short stories is 54.9 (54.9%), increased in the first cycle to 65.7 (65.7%), and in the second cycle the average score again increased to 78.1 (78.1%). So, the ability to write short stories of students from the pretest to the end of the first cycle increased by 10.7 (10.7%), and from the first cycle to the end of the second cycle, it increased by 12.4 (12.4%). Based on the scores above, it can be concluded that starting from before the action to after the action, the students' short story writing skill scores have increased by 23.1 (23.1%) from a score of 54.9 (54.9%) to 78, 1 (78.1%). The improvement of the process can be seen from the condition of students who show positive behavior changes. In cycle II, the condition of the class can be controlled and more conducive. Students who are less motivated seem more enthusiastic, more confident and play an active role in learning to write short stories with problem-based learning strategies, because they can help students bring out writing potential in students and make it easier for students to find ideas taken from the problems around them. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan peningkatan kemampuan menulis cerpen siswa Kelas XI MIPA 4 MAN 2 Brebes dalam pembelajaran menulis cerpen melalui penggunaan strategi pembelajaran berbasis masalah. Hasil penelitian ini menunjukkan, rata-rata skor menulis cerpen pratindakan sebesar 54,9 (54,9%), meningkat pada siklus I menjadi 65,7 (65,7%), dan pada siklus II nilai rata-rata skor kembali meningkat menjadi 78,1 (78,1%). Jadi, kemampuan menulis cerpen siswa dari pretes sampai akhir siklus I mengalami peningkatan sebesar 10,7 (10,7%), dan dari siklus I sampai akhir siklus II mengalami peningkatan sebesar 12,4 (12,4%). Berdasarkan perolehan skor di atas, dapat disimpulkan bahwa mulai dari sebelum tindakan hingga sesudah tindakan, nilai keterampilan menulis cerpen siswa telah mengalami peningkatan sebesar 23,1 (23,1%) yaitu dari skor 54,9 (54,9%) menjadi 78,1 (78,1%). Peningkatan proses dapat dilihat dari kondisi siswa yang menunjukkan perubahan perilaku positif. Pada siklus II, kondisi kelas sudah dapat dikendalikan dan lebih kondusif. Siswa yang kurang termotivasi tampak lebih bersemangat, lebih percaya diri dan berperan aktif mengikuti pembelajaran menulis cerpen dengan strategi pembelajaran berbasis masalah, karena dapat membantu siswa memunculkan potensi menulis dalam diri siswa dan mempermudah siswa dalam menemukan ide yang diambil dari masalah yang ada di sekitar mereka.